MODEL STRATEGI KOPERASI SYARIAH BAYTUL IKHTIAR DALAM PEMBERDAYAAN EKONOMI UMMAT DI KOTA BOGOR - Mitra; Casmita Pujiharto, Yaya Ruhenda; Sumengkar , Apung (ALAMIAH : Jurnal Muamalah dan Ekonomi Syariah, 2025)
This study is entitled "Strategy model of Baytul Ikhtiar Sharia Cooperative in empowering the economy of the people in Bogor City" This study aims to examine the strategy model of Baytul Ikhtiar Sharia Cooperative in empowering the economy of the people in Bogor City. By using qualitative methods and SWOT analysis, this study found that the strategy model used is based on sharia finance, mentoring MSME members and optimizing social funds (ZISWAF and Qardhul Hasan) with the Grameen Bank concept, while the factors that influence it are the Implementation of Sharia Principles, Digitalization Support, Mentoring and Training of MSMEs, Optimization of Social Funds (ZISWAF & Qardhul Hasan), Collaboration with Sharia Financial Institutions and partners, Strong Networks and Communities. However, there are several major challenges faced, such as limited capital and competition. The SWOT analysis reveals that the main strengths lie in cooperative services, Mentoring and training, and optimizing social funds in empowerment programs. However, weaknesses such as limited capital, and lots of competition. Opportunities include government support and collaboration with other institutions, increasing public awareness, while threats include economic instability and policy changes, lack of trust in Islamic cooperatives, and competition between other institutions.